Prescribing patterns of antidepressants among depressive men in Malaysia: A survey - Fata Nahas, Abdul Rahman; Syed Sulaiman, Syed Azhar (EManuscript Services, 2018)
Objective: In recent studies on the prescribing pattern of antidepressants, selective serotonin reuptake inhibitors (SSRIs) were the most prescribed antidepressants in many countries. Yet, little reports investigated depressive populations for antidepressants prescribing in Malaysia. Therefore, this study aimed to explore the pattern of prescribed antidepressants in a Malaysian group of depressive patients throughout their years of depression. Method: A cross-sectional study was conducted on 119 adult male depressive outpatients who were recruited from three psychiatric centers. Patients’ age and duration of depression were recorded, as well as their current and past antidepressants prescribed. Results: Of the study participants, 107 patients (89.9%) were currently antidepressant-treated. Mean age of patients was 49.9 (SD=11.0), while mean duration of depression was 7.8 years (SD=6.1). Markedly, SSRIs were the most currently prescribed antidepressants (72.9%), followed by tricyclic antidepressants (TCAs; 10.3%). Moreover, SSRIs predominated the prescribed antidepressants over the years of depression. Additionally, there was an increase in the share of SSRIs prescribing during these years in the expenses of other antidepressants, especially TCAs, whose prescription share fell from 34.1%, in the years preceding 2005, to only 10.3% in the current time. Conclusion: In sum, this study findings concur several reports from various countries, in which SSRI were the most frequent prescribed antidepressants and their prescribing was increasing over nearly the last 10 years. Further research is advocated to explore these findings in larger depression populations.